Maintenance of species boundaries despite ongoing gene flow in ragworts - Osborne, O; Chapman, M; Filatov, D; al., E (Oxford University Press, 2016)
The role of hybridization between diversifying species has been the focus of a huge amount of recent evolutionary research. While gene flow can prevent speciation or initiate species collapse, it can also generate new hybrid species. Similarly, while adaptive divergence can be wiped out by gene flow, new adaptive variation can be introduced via introgression. The relative frequency of these outcomes, and indeed the frequency of hybridization and introgression in general are largely unknown. One group of closely-related species with several documented cases of hybridization is the Mediterranean ragwort (genus: Senecio) species-complex. Examples of both polyploid and homoploid hybrid speciation are known in the clade, although their evolutionary relationships and the general frequency of introgressive hybridization among them remain unknown. Using a whole genome gene–space dataset comprising eight Senecio species we fully resolve the phylogeny of these species for the first time despite phylogenetic incongruence across the genome. Using a D-statistic approach, we demonstrate previously unknown cases of introgressive hybridization between multiple pairs of taxa across the species tree. This is an important step in establishing these species as a study system for diversification with gene flow, and suggests that introgressive hybridization may be a widespread and important process in plant evolution.